Problematika Akad Nikah Via Daring dan Penyelenggaraan Walimah Selama Masa Pandemi Covid-19 - Mahardika Putera Emas (Batulis Civil Law Review, 2020)
The implementation of marriages during the Covid-19 pandemic was hampered, so that there were adjustments in the marriage ceremony, in this case the marriage contract and the holding of a walimah so that it could be held. The development of increasingly sophisticated technology is the intermediary. One of them is to do a marriage contract online through a video call application. The purpose of this research is to study and analyze the validity of the implementation of online marriage contracts and the holding of walimah during the pandemic, so that a concrete solution must be found. The research method is normative legal research, with a statutory approach, conceptual approach and case approach. The results of the study show that online or online marriage contracts using internet-based video call applications cannot be permitted, this is due to the physical obligation of ittihad majelis (unified assemblies). Postponement of holding the walimah during the Covid-19 pandemic in order to avoid crowds of people, by paying attention to the principles of fiqh. The solution is for the marriage contract in the covid-19 pandemic season, which is to carry out the marriage contract in the way that the prospective groom is represented in the marriage contract process, while holding the walimah distributing food to neighbors and those in need.